HAVESTADT V/S FEBRÉS. ABOUT A LETTER AND SOME SONGS - Rondón Sepúlveda, Víctor (Revista de Historia Social y de las Mentalidades, 2024)
This article examines the relationship between  two treatises on mapudungún (mapuche language)  published by a German Jesuit (Havestadt, 1777)  and a Spanish Jesuit (Febrés, 1765), both active  in Chile during the two decades prior to the  expulsion of the order . From a letter allegedly  written by one of them to the other and the songs  contained in their works, this paper examines the  plans of Compañía de Jesús in this period and  the personal situations of the two missionaries.  Although the Havestadt’s work was previous,  the jesuit superiority it would have preferred the  publication of Febrés’s text due to its closest  relation with the strategy that was implemented in  the years prior to the expulsion order.
Keywords: Havestadt; Febrés; Treatises on mapudungún; Jesuit missionaries; Catechismal songs